O pedagogo José de Barcellos e a formação do professor primário no Ceará (1856-1891) - Feitosa, Adriana Madja dos Santos (2024)
It is addressed to the trajectory, as teacher and principal, of José de Barcellos (1856-1891) who established the first Normal School of Ceará (Escola Normal do Ceará) between the Imperial State and the then recently founded Republic. The general aim of this study is to examine the links between José de Barcellos' educational and professional background and the movement to renew teacher training and primary education. It is classified as qualitative, based on historical science, mediated by biographical and life history studies. Data collection was based on the analysis of sources in the collections of the National Library (BN), Hemeroteca Digital, Instituto do Ceará (IC), Academia Cearense de Letras (ACL) and Biblioteca Estadual do Ceará (BECE), and in the CAPES Catalog of Theses and Dissertations. The findings consisted of theses, dissertations, articles, books, newspapers, magazines, pedagogical manuals, literary books, images and official documents from the time. The findings consisted of theses, essays, articles, books, journals, magazines, pedagogical manuals, literary books, images and official documents of the time. The results point that the life of José de Barcellos was traversed by the context in which he lived, in special, when he lived in the capital city, Fortaleza, center of commerce and cultural life and refugee of retreatants which seeked it aiming to survive in the extended periods of drought. Barcellos made himself present in socio educational context for the implementation of proposals in the organization of elementary education and in the habilitation of the teaching staff. He worked as translator and writer on the O Ceará and Gazeta do Norte newspapers and in the Quinzena magazine and was one of the founding members of the Academia Cearense de Letras. His formative itineraries of adjunct teacher until his habilitations as pedagogue on the Normal School of Brussels, added to the trips for national and international studies qualified him to be the first professor of Pedagogy and Methodology and the director of the Escola Normal. The renowned pedagogist was one of the reformers of primary education, with a new training model that was in force until the 1990s in Ceará. The links between the career of José de Barcellos and the teaching renovation movement lie in the spaces of social, cultural and political interaction and circulation.